Histopathological observation and HSP genes expression analysis of Puccinia triticina under high-temperature stress in Jinmai region - Zhao, Yaqiong; Guan, Yashi; Liu, Miaomiao; Gong, Weiwei; He, Fuxin; Liu, Minjie (Frontiers in Microbiology, 2025)
IntroductionWheat leaf rust is one of the most significant diseases affecting wheat. With the increase of global average temperature, the areas where wheat leaf rust can survive winter and persist through summer have been expanding. And high-temperature resistant isolates were identified within the natural population.MethodsIn this study, two high-temperature resistant strains and two temperature-sensitive strains were selected from 41 isolates collected from Shanxi Province between 2021 and 2022. The analysis of disease severity differences among the four strains at different temperatures revealed that the differences were most significant at 26°C (p < 0.05). Therefore 26°C was selected as the optimal temperature for high-temperature stress. Subsequently, histopathological observations were conducted on the four Pt strains, and the expression levels of five genes were determined, including PtHsp90-1, PtHp, PtHspHSS1, PtHsp60 and PtHspSSB.ResultsHistopathological observations showed that compared with the temperature-sensitive strains, the number of haustorial mother cells and haustoria of high-temperature resistant was not significantly affected by high-temperature stress (p < 0.05). However, the number of hyphal branches of four strains was less affected, indicating that formation of haustorial mother cells and haustoria were the key stages in resistance to heat stress. Further analysis revealed that the expression of five genes reached their maximum at 6 hpi under high-temperature stress. The results indicated that HSP genes play a crucial role in high-temperature resistance during the germination stage of Pt urediospores.DiscussionHowever, the specific molecular mechanism in wheat leaf rust required further study and verification. In conclusion, the early germination of urediospores (0–12 h) and the formation of haustorial mother cells and haustoria (12–24 h) were key stages in resisting high-temperature stress in wheat leaf rust.